Investigation of β‐hydroxybutyrate in early lactation of Simmental cows: Genetic parameters and genomic predictions. (28th June 2021) - Falchi, Laura; Gaspa, Giustino; Cesarani, Alberto; Correddu, Fabio; Degano, Lorenzo; Vicario, Daniele; Lourenco, Daniela; Macciotta, Nicolò P. P.
Abstract: Genomic information allows for a more accurate calculation of relationships among animals than the pedigree information, leading to an increase in accuracy of breeding values. Here, we used pedigree‐based and single‐step genomic approaches to estimate variance components and breeding values for β‐hydroxybutyrate milk content (BHB). Additionally, we performed a genome‐wide association study (GWAS) to depict its genetic architecture. BHB concentrations within the first 90 days of lactation, estimated from milk medium infrared spectra, were available for 30, 461 cows (70, 984 records). Genotypes at 42, 152 loci were available for 9, 123 animals. Low heritabilities were found for BHB using pedigree‐based (0.09 ± 0.01) and genomic (0.10 ± 0.01) approaches. Genetic correlation between BHB and milk traits ranged from −0.27 ± 0.06 (BHB and protein percentage) to 0.13 ± 0.07 (BHB and fat‐to‐protein ratio) using pedigree and from −0.26 ± 0.05 (BHB and protein percentage) to 0.13 ± 0.06 (BHB and fat‐to‐protein ratio) using genomics. Breeding values were validated for 344 genotyped cows using linear regression method. The genomic EBV (GEBV) had greater accuracy (0.51 vs. 0.45) and regression coefficient (0.98 vs. 0.95) compared to EBV. The correlation between two subsequent evaluations, without and with phenotypes for validation cows, was 0.85 for GEBV and 0.82 for EBV. Predictive ability (correlation between (G)EBV and adjusted phenotypes) was greater when genomic information was used (0.38) than in the pedigree‐based approach (0.31). Validation statistics in the pairwise two‐trait models (milk yield, fat and protein percentage, urea, fat/protein ratio, lactose and logarithmic transformation of somatic cells count) were very similar to the ones highlighted for the single‐trait model. The GWAS allowed discovering four significant markers located on BTA20 (57.5–58.2 Mb), where the ANKH gene is mapped. This gene has been associated with lactose, alpha‐lactalbumin and BHB. Results of this study confirmed the usefulness of genomic information to provide more accurate variance components and breeding values, and important insights about the genomic determination of BHB milk content.